1974
DOI: 10.1111/j.1699-0463.1974.tb02338.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOCHEMICAL AND SEROLOGICAL PROPERTIES OF STREPTOCOCCUS MUTANS FROM VARIOUS HUMAN AND ANIMAL SOURCES

Abstract: The main part of strains of Streptococcus mutans isolated from the present Danish material of blood from patients with subacute endocarditis and from human teeth belonged to two of five serotypes established by Bratthall, viz. type c and type e. Two new types were established: type f and type g. Strain SL‐1 seems to constitute a distinct type. Strains of serotypes a and b have not been isolated in Denmark, and strains of serotypes d, g and SL have been isolated from teeth only. The registered differences in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(13 citation statements)
references
References 17 publications
1
11
1
Order By: Relevance
“…Most of the studies, however, have reported the occurrence of serotype e with highest prevalence that ranged from 2% to 30% followed by serotypes: f and k in the range of 1-25% and around 5% respectively [Table 2]. [171819202122232425262728] Since the findings of our study are in contrary to those that have been observed earlier, we speculate that this could be due to a shift in S. mutans serotype in subjects from this region. Such serotype shifts have been reported elsewhere in other strains such as Streptoccocus agalactiae from Group B Streptococcus for example, where in S. agalactiae serotype Ia was found to occur consistently with a higher prevalence in North American population relative to those from other geographic regions ( P < 0.005).…”
Section: Discussioncontrasting
confidence: 94%
“…Most of the studies, however, have reported the occurrence of serotype e with highest prevalence that ranged from 2% to 30% followed by serotypes: f and k in the range of 1-25% and around 5% respectively [Table 2]. [171819202122232425262728] Since the findings of our study are in contrary to those that have been observed earlier, we speculate that this could be due to a shift in S. mutans serotype in subjects from this region. Such serotype shifts have been reported elsewhere in other strains such as Streptoccocus agalactiae from Group B Streptococcus for example, where in S. agalactiae serotype Ia was found to occur consistently with a higher prevalence in North American population relative to those from other geographic regions ( P < 0.005).…”
Section: Discussioncontrasting
confidence: 94%
“…S.m. group consists of 7 species that can be classified into 9 serotypes on the basis of saccharide antigens (Table III) (Facklam 2002;Perch et al 1974;Nakano et al 2007). …”
Section: Streptococcus Mutans Groupmentioning
confidence: 99%
“…In addition, detection sensitivity has been shown to be higher with such a PCR method as compared to a conventional immunodiffusion technique [32]. The detection rate of serotype c strains has been reported to be the highest (ranging from 64.5 to 89.3%), followed by serotype e (from 7.0 to 26.1%) ( Table 2) [29,[31][32][33][34][35][36][37][38][39][40][41][42][43]. In contrast, the detection rate of serotype f is estimated to be less than 5%, based on the results of previous studies, though a higher frequency was reported in early studies.…”
Section: Serotypes Of S Mutansmentioning
confidence: 99%
“…The prevalence rates of serotypes of S. mutans presented in past articles are summarized in Table 2 [29,[31][32][33][34][35][36][37][38][39][40][41][42][43]. There are several methods used to determine serotypes, among which an immunodiffusion method using cell extract antigens and serotype-specific antisera is commonly utilized.…”
Section: Serotypes Of S Mutansmentioning
confidence: 99%